Keefektifan Model Pembelajaran Number Head Together (NHT) Berbantu Media Puzzle Terhadap Hasil Belajar Matematika - Kurnia, Veni Tri; Damayani, Aries Tika (Universitas Pendidikan Ganesha, 2019)
This study aims to identify the effectiveness of the Puzzle Media Number Head Together (NHT) learning model on Mathematics learning outcomes of fourth grade students of SDN 01 Damarjati Jepara. This type of research is quantitative research. The research design used in this study is Pre-Experimental Design in the form of One Group Pretest-Posttest Design. The population of this study was all fourth grade students of SDN 01 Damarjati Jepara using the Non Probability Sampling technique which is a type of saturated sampling. Data in this study were obtained through tests, documentation and interviews. Data analysis using the analysis of the final initial normality test and hypothesis testing (t test). normality test is used to find out the student learning outcomes are normally distributed or not. Hypothesis testing using t-test. Based on the results of the research data analysis, the t test coefficient is 14,175 and the coefficient is significant at the level of 5%. The average value before being given treatment is 51 which means less than KKM and the average value after being given treatment is 78 which means it has fulfilled the KKM. The difference in average increases is 27. Therefore, it can be concluded that the use of Media Puzzle Assisted Number Head Together (NHT) learning model is effective for Mathematics learning outcomes of fourth grade students of SDN 01 Damarjati Jepara academic year 2018/2019.